Analisis Perbandingan Tindak Tutur Lokusi dan Perlokusi Antara Dokter Spesialis dan Dokter Umum dalam Interaksi dengan Pasien - Febri Simamora; Grace Tampubolon; Hanna Sianturi; Hikmah Sidabutar; Nopita Silaban; Osmer Nadeak; Pintauli Silaban (INDO PUBLISHING, 2025)
Communication between healthcare providers and patients plays a crucial role in ensuring the quality of healthcare services. This article explores the importance of effective communication in medical interactions and highlights how communication failures can negatively impact diagnosis, treatment, and patient satisfaction. Using a pragmatic approach—specifically speech act theory as introduced by John L. Austin and further developed by John R. Searle—the article analyzes medical utterances as communicative acts with specific intentions and effects. The discussion includes classifications of locutionary, illocutionary, and perlocutionary acts, as well as types of speech acts such as representative, directive, commissive, expressive, and declarative. The study emphasizes that a deep understanding of speech acts can enhance the effectiveness of medical communication, especially in the context of cultural and social dynamics, and contribute to a more holistic approach to healthcare delivery.